Impact of Hemoglobin Levels and Anemia on Mortality in Acute Stroke: Analysis of UK Regional Registry Data, Systematic Review, and Meta‐Analysis. Issue 8 (17th August 2016) - Barlas, Raphae S.; Honney, Katie; Loke, Yoon K.; McCall, Stephen J.; Bettencourt‐Silva, Joao H.; Clark, Allan B.; Bowles, Kristian M.; Metcalf, Anthony K.; Mamas, Mamas A.; Potter, John F.; Myint, Phyo K.
Abstract : Background: The impact of hemoglobin levels and anemia on stroke mortality remains controversial. We aimed to systematically assess this association and quantify the evidence. Methods and Results: We analyzed data from a cohort of 8013 stroke patients (mean±SD, 77.81±11.83 years) consecutively admitted over 11 years (January 2003 to May 2015) using a UK Regional Stroke Register. The impact of hemoglobin levels and anemia on mortality was assessed by sex‐specific values at different time points (7 and 14 days; 1, 3, and 6 months; 1 year) using multiple regression models controlling for confounders. Anemia was present in 24.5% of the cohort on admission and was associated with increased odds of mortality at most of the time points examined up to 1 year following stroke. The association was less consistent for men with hemorrhagic stroke. Elevated hemoglobin was also associated with increased mortality, mainly within the first month. We then conducted a systematic review using the Embase and Medline databases. Twenty studies met the inclusion criteria. When combined with the cohort from the current study, the pooled population had 29 943 patients with stroke. The evidence base was quantified in a meta‐analysis. Anemia on admission was found to be associated with an increased risk of mortality in both ischemic stroke (8 studies; odds ratio 1.97 [95% CI 1.57–2.47]) and hemorrhagic stroke (4 studies; odds ratio 1.46 [95% CI 1.23–1.74]). Conclusions: Strong evidence suggests that patients with anemia have increased mortality with stroke. Targeted interventions in this patient population may improve outcomes and require further evaluation.